Editorial - Calizaya Calizaya, Hugo (2020)
The Graduate School of the Private University of Tacna, has been promoting research processes leading to its social integration with the national and regional environment. We believe that it is necessary to assume that the training and academic institutions have, within their scientific and technological role, the transfer of knowledge to improve the quality of life of their society. The masters, all linked to the needs of the environment, subscribe to the possibility of being protagonists of changes in their respective areas of competence and relevance through research and innovation. Thus, institutions must fulfill one of the most important purposes in the investigative process, that of improving their capacities for greater visibility. Veritas et Scientia, has set out as a development objective to disseminate its work through the OJS platform, which we have already been doing, and improve the indicators that allow it to access the Latindex 2.0 and Scielo community. We know that it is a task that demands a systematic and responsible order of the processes, and in that our editorial team and related collaborators, already put their best effort.We believe that in a reasonable time the objectives set will become possible and that the Tacneña community may have one more space for the dissemination of its research, technological and innovation efforts. Dr. Hugo Calizaya Calizaya Director – Editor Veritas Et Scientia